Prognostic Role of Secretory Clusterin in Multiple Human Malignant Neoplasms: A Meta-Analysis of 26 Immunohistochemistry Studies - Zhang, Jianzhong (PLoS One, 2016)
Secretory clusterin (sCLU) is a potential prognostic tumour biomarker, but results of different sCLU studies are inconsistent. We conducted this meta-analysis to evaluate the precise predictive value of sCLU. Qualified studies were identified by performing online searches in PubMed, EMBASE, and Web of Science. The selected articles were divided into three groups based on scoring method for clusterin detection. Pooled hazard ratios (HRs) with 95% confidence interval (CI) for patient survival and disease recurrence were calculated to determine the correlation between sCLU expression and cancer prognosis. Heterogeneity was assessed using I(2) statistics, and specific heterogeneity in different groups was analysed. Elevated sCLU was significantly associated with recurrence-free survival in groups 1 and 3 (group 1: pooled HR = 1.35, 95% CI = 1.01 to 1.79; group 3: pooled HR = 1.80, 95% CI = 1.22 to 2.65). However, clusterin expression was not associated with overall survival in all three groups. Results showed that only the heterogeneity of group 2 was very strong (p = 0.013, I(2) = 76.3%), in which the specimens were scored through sCLU staining intensity only. sCLU is a potential biomarker for tumour prognosis, and IHC methods can be more standardised if both intensity and staining proportion are considered.